Optimizing Colorectal Surgery Outcomes: The Role of the Advanced Practice Provider (APP) in Developing a Center for Pelvic Floor Disorders and Maximizing Scope of Practice for APPs - Bonnette, Holly; Savitt, Lieba R. (Clinics in Colon and Rectal Surgery, 2025)
Many patients with pelvic floor disorders who are referred to colorectal surgery do not actually need surgery. The Massachusetts General Hospital (MGH) Center for Pelvic Floor Disorders (PFDC) was established in 2008 out of a recognition of the need for a specialized comprehensive treatment for patients living with a pelvic floor disorder. To describe the model that we have created utilizing advanced practice providers (APPs) within the PFDC at the MGH as an example of a model of care for patients who historically may have been managed by colorectal surgeons. The utilization of APPs in surgery has increased, which in turn has had positive effects on patient care and can help reduce the demands put on surgeons to see patients who ultimately do not end up having surgery. There is also a potential for both direct and indirect revenue production through the utilization of APPs at the top of their scope of practice as well as increased access to care for these patients. Training APPs to work at the top of their scope within a surgical practice increases patient's access to care, allows surgeons to focus on those who ultimately require surgery, and can lead to better patient outcomes at a reduced healthcare cost. In order for this symbiotic relationship between APPs and surgeons to be successful, it is essential that there is mutual collaboration and trust between providers. It requires commitment from surgeons to appropriately train their APPs.
Keywords: pelvic floor disorders; advanced practice providers (APPs); colorectal surgery; center for pelvic floor disorders (PFDC)